Electrocardiographic Studies In Congestive Heart Failure In Dogs - B. R., Deepti; Yathiraj, S.; Ramesh, P. T.; Kamran, C. A.; Ranganath, L.; Narayanaswamy , H. D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Electrocardiographic abnormalities in dogs with congestive heart failure presented to Veterinary College, Bangalore were studied. Abnormalities included rhythm and morphological changes. The abnormalities of rhythm were seen in 49 cases and they were sinus and ventricular tachycardia, atrial flutter and fibrillation, atrial and ventricular premature complexes and right bundle branch block. The abnormalities of morphology pattern in 17 dogs were tall R and T waves, deep Q and S waves, small R waves and ST segment sagging.
Keywords: Dog; congestive heart failure; electrocardiography